PENGEMBANGAN NILAI KEDISIPLINAN KUDA KENCAK UNTUK MENGURANGI DISONANSI KOGNITIF SISWA MTs NAHDLATUTH THALABAH - Wulandari, Ilma Rizqina; Isriyah, Mudafiatun; Fauziyah, Nailul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop educational media or a guidance service module that integrates cultural values, particularly the value of discipline embedded in the kuda kencak tradition, to reduce cognitive dissonance among students at MTs Nahdlatuth Thalabah. Cognitive dissonance refers to a psychological condition characterized by discomfort resulting from a conflict between beliefs and behaviors or between two contradictory beliefs. In the educational context, such dissonance may occur when students or educators encounter inconsistencies between their personal beliefs and newly acquired information, potentially affecting motivation and learning outcomes. The research employs a research and development (R&D) methodology using a mixed-method approach that combines qualitative and quantitative techniques. The qualitative approach is used to explore and implement the cultural values of kuda kencak as part of character education, with a focus on promoting discipline. These values are expected to help students address internal conflicts arising from contradictory beliefs or behaviors. Meanwhile, the quantitative analysis indicates a statistically significant difference between pre-test and post-test results, with a p-value of 0,03125. The findings suggest that the guidance module based on the disciplinary values of kuda kencak culture is effective in reducing students' cognitive dissonance, enhancing emotional balance, and strengthening their personal beliefs.